(3GdaJhMGJ GdEdgjI aj faY CQhGM GdPhGJ GdEfSGfjIs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s ((3Cejf Hf NjQ Gddg GdYeQi GdNWjH s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf hdG YOhGf Edi Ydi GdXGdejf hHYO agPG eNJUQ ai GdJUha SejJg GdaJhMGJ GdEdgjg eTJedI Ydi YTQI aUhd GdChd ai HjGf JYQja GdJUha s
(3BNQgG (B:s
(3hSGFQ GdCfHjGA Ydi fHjfG hYdjge Cced GdUdGI hGdSdGe hGdBd cd hSGFQ GdUGdMjf hGdeSdejf CLeYjf bGd GdeDda JeJ GdaJhMGJ GdEdgjI ai faY CQhGM GdPGJ GdEfSGfjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B46 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B182 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B374s
Keywords: (3GdeLGejYs